Emergency Department Utilization Is Low After Outpatient Elective Rotator Cuff Repair. Issue 5 (1st March 2022) - Raji, Yazdan; Vakharia, Ajit M.; Chen, Mingda; Sivasundaram, Lakshmanan; Wang, Joanne H.; Salata, Michael J.; Voos, James E.; Gillespie, Robert J.
Abstract : Introduction: The purpose of this study was to establish emergency department (ED) utilization rate and reasons for presentation to the ED after outpatient rotator cuff repair (RCR) and determine preoperative predictors for these ED visits. Methods: Patients who underwent outpatient RCR between 2014 and 2015 were retrospectively evaluated using the New York and Florida State Databases. The primary outcome was all-cause 7- and 30-day ED utilization rates. Reasons for presentation to the ED were recorded and stratified. Univariate and multivariate analyses were done to identify independent predictors of ED utilization. Results: The 7- and 30-day ED visit rates were 3.2% and 5.0%, respectively. The most common cause for an ED visit after outpatient RCR at 7- and 30-days postoperatively were postoperative pain (29.0%) and GI complaints (16.3%), respectively. African American race (odds ratio [OD], 1.69; P < 0.001), Hispanic race (OD, 1.47; P = 0.005), and comorbid diagnoses of hypertension (OD, 1.51; P < 0.001), diabetes (OD, 1.58; P < 0.001), and/or schizophrenia (OD, 5.14; P < 0.001) were independent risk factors for an ED visit at up to 30 days postoperatively. Those with Medicare (OD, 2.01; P < 0.001) or Medicaid (OD, 2.61; P < 0.001) were more than twice as likely to present to the ED within 30 days than those with private health insurance. Discussion: ED utilization after outpatient RCR is uncommon with postoperative pain as the most common chief concern for ED visits within the first 7 days and GI issues as the most common reason for ED encounters at up to 30 days postoperatively. Hypertension, diabetes, renal failure, liver disease, rheumatologic diseases, schizophrenia, depression, and Medicare and Medicaid insurance were independent predictors of ED encounters at up to 30 days postoperatively. Procedures done at freestanding surgery centers were protective against ED utilization. Level of Evidence: Level III, Retrospective Cohort